Angular in Action - Wilken, Jeremy (Manning Publications, 2018)
Angular in Action teaches you everything you need to build production-ready Angular applications. You'll start coding immediately, as you move from the basics to advanced techniques like testing, dependency injection, and performance tuning. Along the way, you'll take advantage of TypeScript and ES2015 features to write clear, well-architected code. Thoroughly practical and packed with tricks and tips, this hands-on tutorial is perfect for web devs ready to build web applications that can handle whatever you throw at them.